HUBUNGAN ANTARA PEMAHAMAN PERATURAN PERMAINAN FUTSAL DENGAN KINERJA WASIT FUTSAL SAAT MEMIMPIN PERTANDINGAN - Muhamad Luthfi Fadillah; Nuryadi Nuryadi; Didin Budiman (Jurnal Speed (Sport, Physical Education, Empowerment), 2020)
This research comes from the problem of a futsal referee when lead the competition and make a basic trouble because lack of comprehension regarding the rule of futsal itself. This things makes the referee performance does not maximum when lead the competition. The goal of the research is to know the relations between comprehension of futsal rule with Referee performance of asprov PSSI west java  when lead the competition. The method that used in this research is descriptive method. The sample and population that used in this research is 19 registered referees that has National license in AsprovPSSI West Java using saturated sampling. The instrument that used is questionnaire that consists of questions about play rules and observation which refers to referee assessment format from PSSI. The result shows that there is significant relation between comprehensioni of futsal rules with Referee performance of asprov PSSI west java when lead the competition with the correlation coefficient value 0.702 that categorized as sufficient. The writer suggest the AsprovPSSI West Java referee to defend and increase the comprehension level regarding rules play and referee performance in order to increase the quality in leading the futsal competition. Keywords: Understanding Law Of The Game, Referee Performance